IMPLEMENTATION OF THEORY OF CONSTRAINT ON WAITING TIME OF PRESCRIPTION SERVICE - Alissa Sita Pertiwi; Thinni Nurul Rochmah (Universitas Airlangga, 2019)
Background: Medical services provided within the Indonesian National Health Insurance programme or Jaminan Kesehatan Nasional (JKN) have been continuously improving for the past several years. One of them is pharmaceutical service in the Pharmacy Store for JKN patients at one hospital with the highest number of visitors in Surabaya. However, one preliminary study points out that patient waiting time for prescription services in the Pharmacy Store for JKN patients is longer than the national standard.Aim: This study aims to investigate the causes for such delay in prescription services as one of pharmaceutical services in the Pharmacy Store for JKN patients at one hospital in Surabaya.Methods: This is an observational descriptive research with a reference to the Theory of Constraints. The research was conducted from August 2017 to February 2018. The data were obtained from observations, interviews with one pharmacist and four pharmacy technicians, and waiting time for prescription service. Results: The study finds that the longer waiting time is caused by inefficient division of jobs and workers and the lack of worker’s discipline to work on time. The behaviors and habits of pharmacist and pharmacy technicians in drug preparation greatly affect patient waiting time, since the services still highly depend on manual human labor.Conclusions: Patient experience in prescription drug services is significantly influenced by the time spent waiting for the service provider. This study provides useful insights about constraint identification in pharmaceutical services, especially waiting time.Keywords: Pharmaceutical service, Theory of Constraints, Patient waiting time.